2010
DOI: 10.1111/j.1558-5646.2010.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Gene Movement to the “Two Rules of Speciation”

Abstract: The two "rules of speciation"-the Large X-effect and Haldane's rule-hold throughout the animal kingdom, but the underlying genetic mechanisms that cause them are still unclear. Two predominant explanations-the "dominance theory" and faster male evolution-both have some empirical support, suggesting that the genetic basis of these rules is likely multifarious. We revisit one historical explanation for these rules, based on dysfunctional genetic interactions involving genes recently moved between chromosomes. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 94 publications
(142 reference statements)
2
39
0
Order By: Relevance
“…Across all types of transpositions, we found that there was an overall excess of genes moving off the X chromosome (Table S9), consistent with previous findings (Betrán et al 2002;Bai et al 2007;Meisel et al 2009;Vibranovski et al 2009). However, there has been some disagreement about whether this pattern applies to all duplicates or just those formed by retrotransposition and how it varies between duplicative transpositions and relocations Meisel et al 2009;Vibranovski et al 2009;Moyle et al 2010;Zhang et al 2010). Our results contain the largest set of gene transpositions to date and should be able to provide a definitive answer.…”
Section: Bias In the Direction Of The Movementsmentioning
confidence: 83%
See 2 more Smart Citations
“…Across all types of transpositions, we found that there was an overall excess of genes moving off the X chromosome (Table S9), consistent with previous findings (Betrán et al 2002;Bai et al 2007;Meisel et al 2009;Vibranovski et al 2009). However, there has been some disagreement about whether this pattern applies to all duplicates or just those formed by retrotransposition and how it varies between duplicative transpositions and relocations Meisel et al 2009;Vibranovski et al 2009;Moyle et al 2010;Zhang et al 2010). Our results contain the largest set of gene transpositions to date and should be able to provide a definitive answer.…”
Section: Bias In the Direction Of The Movementsmentioning
confidence: 83%
“…However, this last study has been criticized on the grounds that too few instances of DNA-based transpositions were found for conclusive inference (Zhang et al 2010). The same patterns of movement are repeated in mammals, with an excess of X-to-autosome gene movements for RNA-based duplicative transpositions (Emerson et al 2004;Potrzebowski et al 2008) and for DNA-based relocations (Moyle et al 2010), but not for DNA-based duplications (Jiang et al 2007;). There are several hypotheses that attempt to explain the excess of Xto-autosome gene traffic, including sexually antagonistic selection (Rice 1984;Wu and Xu 2003;Connallon and Clark 2011), escape from X inactivation (Betrán et al 2002), meiotic drive (Meiklejohn and Tao 2010), and dosage compensation (Bachtrog et al 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Duplication and differentiation between paralogs can alter the genetic architecture of male and female traits, and hybridization between species can potentially disrupt the transmission of sex-specific genes, leading to sex-specific hybrid inviability or sterility (see Lynch and Force 2000;Masly et al 2006). Gene duplication between chromosomes, particularly the movement of male functions from the X to the autosomes, can disproportionately affect males and might partially account for the two rules of speciation (Moyle et al 2010): ''Haldane's rule'' (Haldane 1922;Coyne and Orr 2004) and the ''large-X effect'' (Coyne and Orr 1989;True et al 1996;Tao et al 2003;Masly and Presgraves 2007;Presgraves 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, divergence of meiotic drive suppressor systems (Frank, 1991;Hurst and Pomiankowski, 1991;Tao andHartl, 2003 reviewed in McDermott andNoor, 2010) and other systems of genomic conflict (Johnson, 2010), inherent lability of spermatogenesis (Wu and Davis, 1993), faster X-chromosome evolution (Charlesworth et al, 1987) and Y chromosome and maternal effects (Sawamura, 1996;Turelli and Orr, 2000) have received most attention. In a recent paper, Moyle et al (2010) revisit the old, but largely neglected argument that intragenomic rearrangements may contribute to HR, and they present support for this in mammals, but not Drosophila.…”
Section: Genetic Theoriesmentioning
confidence: 99%